Development of communication models of wireless environment in emergency situations - Pospelov, Boris; Petukhova, Olena; Meleshchenko, Ruslan; Gornostal, Stella; Shcherbak, Sergey (Eastern-European Journal of Enterprise Technologies, 2018)
Two-point communication model of the wireless environment with one-beam and multi-beam propagation of radio waves were developed. The specified models make it possible to create various particular two-point communication models of wireless environment, taking into account the assigned geometry of location of shadowing and scattering structures in the environment. The practical use of the proposed models is limited to arbitrary points of radiation and reception in the environment, taking into account location of directional aerials in them. To study known multipoint technologies under conditions of emergency situations, we developed the multipoint communication models with one-beam and multibeam propagation of radio waves from each radiation point to each reception point, predetermined by the presence of shadowing and scattering structures in the environment. The developed multipoint models make it possible to create specific models at the physical level for various multi-aerial technologies, taking into consideration the use of aerial arrays of arbitrary configuration at the transmitting and receiving sides. Verification of the developed communication models of the wireless environment was performed. It was found that the use of directional aerials at the transmitting and receiving sides of the wireless environment in the presence of considerable shadowing and scattering structures makes it possible to significantly improve noise immunity. It is noted that with the use of the developed communication models, it is possible to carry out in-depth examination of the physical level with a view to developing a reliable and stable architecture of communications under conditions of emergency situations.